Pemanfaatan Handphone untuk Meningkatkan Pemahaman Peserta Didik pada Materi Perangkat Keras Jaringan Komputer - Maria Agustina Diyaning Setyohati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
Mobile phones are currently the primary devices that occupy a central position in people's daily lives. All aspects of human needs are intertwined with mobile phones. They are used for entertainment, economics, transportation, healthcare, and even education. In the realm of learning activities, teachers have started utilizing mobile phones as a medium to support and facilitate the delivery of instructional materials. The research conducted in Class 8A of SMPN 2 Mertoyudan during the academic year 2022/2023 aims to describe the utilization of mobile phones to enhance students' understanding of computer network hardware material. The role of mobile phones in the learning process assists students in searching for relevant materials and supporting information related to the subject matter being taught. The stages of learning conducted in this research include preparation, concept introduction, interactive activities, exercises and evaluation, feedback and monitoring. The research methodology employed is qualitative descriptive, utilizing questionnaire instruments in the form of pretests and posttests. The success criterion established for this research is that students achieve a minimum passing grade (KKM), which is equal to or higher than 77. The research findings indicate that the students' scores improved significantly, as none of the students reached the KKM during the pretest, while 25 out of 32 students achieved the KKM in the posttest. Therefore, it can be concluded that through the utilization of mobile phones, students' understanding of computer network hardware material can be enhanced.